Tobacco Advertisements on Social Media and Religiosity and Its Effect to Smoking Intention in Students Muslim - Yohana Ingrid Lorenza; Putra Apriadi Siregar; Zuhrina Aidha (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
The tobacco industry tries to attract the attention of young people as potential consumers through cigarette advertisements on various platforms, one of which is cigarette advertisements on social media. Cigarette advertisements on social media appear and are broadcast directly or indirectly through television, radio, billboards, and other media. This study aims to determine how the influence of cigarette advertisements on social media and religiosity can affect smoking intentions in adolescents. This study uses quantitative research with a cross-sectional design with a population of 2,203 people and a sample size of 1000 respondents. The sampling technique in this study uses purposive sampling criteria to determine the sample, which includes 11th - 12th-grade students who have social media applications. The variables analyzed include cigarette advertisements (whether or not they have seen cigarette advertisements on social media, intensity, and duration), smoking intention (purchase intention and family smoking behavior), and self-religiosity (intensity of listening to lectures on the law of smoking and duration). This research was conducted at State Aliyah Madrasah 2 Model Medan in January 2024. Primary data came from Google Forms questionnaires distributed directly to students. To test this research, the variables analyzed were cigarette advertising, smoking intention, and religiosity. This study uses a correlation test and multiple linear regression test using SPSS version 20. This study shows the results that cigarette advertisements on social media affect adolescents' intentions regarding smoking behavior (Sig < 0.007), and there is an effect of religiosity on adolescents' intentions regarding smoking behavior (Sig < 0.001). The influence of cigarette advertisements on adolescent smoking intention and the results of religiosity research show that smoking intention is influenced by a lack of self-control and low self-confidence, so the desire to smoke cannot be minimized.Keyword: Religiosity, Smoking intention, Social Media, Teenegers, Tobacco advertisement.